Characteristics of Thyroid Eye Disease Patients at Wahidin Sudirohusodo Hospital Makassar - Jayanti, Usna; Kusumawardhani, Sri Irmandha; Lantara, Andi Millaty Halifah Dirgahayu; Maharani, Ratih Natasha; Namirah, Hanna Aulia (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Thyroid Eye Disease (TED) is an autoimmune orbital disorder frequently associated with Graves’ disease, marked by orbital fat expansion and extraocular muscle swelling that may impair vision and quality of life. Objective: To describe the characteristics of TED patients at RSUP Wahidin Sudirohusodo Makassar based on age, gender, clinical manifestations, management, and smoking history. Methods: A descriptive study of 55 TED patients recorded at RSUP Wahidin Sudirohusodo Makassar. Results: Most patients were aged 20–44 years (60%), followed by 45–64 years (34.55%) and 13–19 years (5.45%), with no cases above 65 years. Females predominated (61.82%). The most common symptom was proptosis (100%), followed by excessive tearing (49.09%), red eyes (27.27%), refractive errors (23.64%), diplopia (10.91%), pain during eye movement (7.27%), and photophobia (7.27%). The main treatment was intravenous methylprednisolone plus thiamazole (47.27%), followed by intravenous methylprednisolone alone (18.18%), thyrozol (18.18%), and propranolol (9.09%). One patient (1.82%) underwent orbital decompression. Active smoking was reported in 32.73% of patients. Conclusion: TED patients were predominantly females aged 20–44 years, with proptosis as the leading manifestation. The most common management was intravenous methylprednisolone combined with thiamazole. Smoking may worsen disease severity